PSYCHOLOGICAL ASPECTS OF PROTECTING UNORGANIZED YOUTH FROM THE INFLUENCE OF DESTRUCTIVE IDEAS - Abdullayeva Dilbar Ubaydullayevna (The American Journal of Social Science and Education Innovations, 2024)
This article highlights the concept of unorganized youth, its psychological interpretation, and the specific psychological aspects of protecting unorganized youth from the effects of destructive ideas.